Enhanced Hole Mobility and Decreased Ion Migration Originated from Interface Engineering for High Quality PSCs with Average FF beyond 80%. Issue 6 (24th April 2022) - Gong, Xiaoli; Li, Haimin; Liu, Xingchong; Zhao, Dewei; Wang, Hanyu; Ni, Yafei; Lei, Yue; Tang, Yanling; Liu, Shuqian
Abstract: Perovskite solar cells (PSCs) have made significant progress in power conversion efficiency (PCE) by optimizing deposition method, composition, interface, etc. Although the two‐step method demonstrates the advantage of being easy to operate, too much residual PbI2 not only forms defect centers, but affects the perovskite crystallization by arising more grain boundaries (GBs) due to the easy‐to‐crystallize nature of PbI2 . And GBs in polycrystalline perovskite usually provide main channel for ion migration, leading to accumulation of charges at the interface to form a barrier, thus reducing carrier mobility and resulting in degradation of perovskite devices. Here, an organic molecule N‐(4‐acetylphenyl)maleimide (N‐APMI) is used to modify interface between perovskite and hole transport layer. X‐ray photoelectron spectroscopy, scanning electron microscope, and nuclear magnetic resonance results show that ketone group (CO) in N‐APMI forms a strong coordination with Pb 2+, which effectively reduces the residual amount of PbI2 nanoparticles on the perovskite surface, giving rise to improved crystallization of perovskite. Temperature‐dependent current response demonstrates that ion migration is effectively suppressed, and hole mobility validly increases from 10.74 to 19.48 cm 2 V –1 s –1, leading to a champion fill factor (FF) of 82.5% (PCE 21.96%), and the maximum PCE of the device improves from 20.09% to 23.03%. Abstract : Coordination of N‐(4‐acetylphenyl)maleimide with Pb 2+ at the interface suppresses ion migration, as indicated by the temperature‐dependent current response. Hole mobility increases from 10.74 to 19.48 cm 2 V −1 s −1 benefiting from the reduction in defects. Device with an average fill factor of over 80% and the maximum power conversion efficiency of 23.03% is achieved.